1999
DOI: 10.1046/j.1365-2249.1999.00770.x
|View full text |Cite
|
Sign up to set email alerts
|

β2-glycoprotein I (β2-GPI) mRNA is expressed by several cell types involved in anti-phospholipid syndrome-related tissue damage

Abstract: SUMMARYWe report here the expression of b 2 -GPI mRNA by cell types involved in the pathophysiology of the anti-phospholipid syndrome (APS), i.e. endothelial cells as a target of autoantibodies in the APS, astrocytes and neurones involved in APS of the central nervous system (CNS). Lymphocytes were also included in the study, as it has been demonstrated that patients with systemic lupus erythematosusassociated CNS diseases have serum anti-lymphocyte antibodies cross-reacting with brain antigens, and intratheca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 43 publications
(60 reference statements)
4
48
2
Order By: Relevance
“…Although it is generally accepted that the protein is present on different endothelial cell membranes (50,51), the results on apoH mRNA expressed by endotheliocytes are conflicting (39,40). Moreover, we did not observe apoH transcripts in endothelial cells.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Although it is generally accepted that the protein is present on different endothelial cell membranes (50,51), the results on apoH mRNA expressed by endotheliocytes are conflicting (39,40). Moreover, we did not observe apoH transcripts in endothelial cells.…”
Section: Discussioncontrasting
confidence: 74%
“…More recently apoH mRNA was found by RT-PCR on RNA extracted from other tissues (intestine, placenta, foetal astrocytes, lymphocytes) or cultured cells (transformed cell lines) such as choriocarcinoma, hepatoma (36), colon adenocarcinoma (35), neuroblastoma, umbilical vein endothelial cells (HUVEC, but not for Alvarado-de la Barrera, 39), astrocytoma, glioblastoma cells (40) and in monocytes (41).…”
Section: Introductionmentioning
confidence: 99%
“…The best described antigen in APS is β-2 glycoprotein I (β 2 GPI). β 2 GPI, a cationic lipid-binding protein with unclear function, is made especially by the liver and circulates at high levels in plasma (50-200 μg/ml) (6,7). It has been suggested that anti-β 2 GPI antibodies potentiate thrombosis by engaging β 2 GPI on cell surfaces, thereby promoting cell activation (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Another property of ␤ 2 -GPI is its ability to bind at the monocyte surface, thus promoting tissue factor and thereby increasing the risk of thrombotic events. 11 ␤ 2 -GPI can also be expressed on the endothelial cell membrane 12 and on macrophages. 13 Among the several candidate ␤ 2 -GPI cell receptors, annexin II, megaline, and apolipoprotein E receptor 2Ј (apoER2Ј) are involved in activating endothelial cells and platelets.…”
Section: Introductionmentioning
confidence: 99%